Жамбатырова Г. Ш. – первый декан факультета международных отношений - Шакиров, К. Н. (International relations and international law Journal, 2016)
Zhambatyrova G. Sh. is the first dean of faculty of the international relations. Жамбатырова Ғ. Ш. - халықаралық қатынастар факультетінің алғашқы деканы